Golden ratio and self-similarity in swimming: breast-stroke and the back-stroke - Verrelli, Cristiano M.; Romagnoli, Cristian; Colistra, Nicolò; Ferretti, Ivo; Annino, Giuseppe; Bonaiuto, Vincenzo; Manzi, Vincenzo (Frontiers in Human Neuroscience, 2023)
Dynamics-on-graph concepts and generalized finite-length Fibonacci sequences have been used to characterize, from a temporal point of view, both human walking & running at a comfortable speed and front-crawl & butterfly swimming strokes at a middle/long distance pace. Such sequences, in which the golden ratio plays a crucial role to describe self-similar patterns, have been found to be subtly experimentally exhibited by healthy (but not pathological) walking subjects and elite swimmers, in terms of durations of gait/stroke-subphases with a clear physical meaning. Corresponding quantitative indices have been able to unveil the resulting hidden time-harmonic and self-similar structures. In this paper we meaningfully extend such latest findings to the remaining two swimming strokes, namely the breast-stroke and the back-stroke: breast-stroke, just like butterfly swimming, is highly technical and involves the complex coordination of the arm and leg actions, while back-stroke is definitely similar to front-crawl swimming. An experimental validation with reference to international-level swimmers is included.